Loss of Col3a1, the Gene for Ehlers-Danlos Syndrome Type IV, Results in Neocortical Dyslamination - Jeong, Sung-Jin; Li, Shihong; Luo, Rong; Strokes, Natalie; Piao, Xianhua (PLOS ONE, 2012)
It has recently been discovered that Collagen III, the encoded protein of the type IV Ehlers-Danlos Syndrome (EDS) gene, is one of the major constituents of the pial basement membrane (BM) and serves as the ligand for GPR56. Mutations in GPR56 cause a severe human brain malformation called bilateral frontoparietal polymicrogyria, in which neurons transmigrate through the BM causing severe mental retardation and frequent seizures. To further characterize the brain phenotype of Col3a1 knockout mice, we performed a detailed histological analysis. We observed a cobblestone-like cortical malformation, with BM breakdown and marginal zone heterotopias in Col3a1−/− mouse brains. Surprisingly, the pial BM appeared intact at early stages of development but starting as early as embryonic day (E) 11.5, prominent BM defects were observed and accompanied by neuronal overmigration. Although collagen III is expressed in meningeal fibroblasts (MFs), Col3a1−/− MFs present no obvious defects. Furthermore, the expression and posttranslational modification of α-dystroglycan was undisturbed in Col3a1−/− mice. Based on the previous finding that mutations in COL3A1 cause type IV EDS, our study indicates a possible common pathological pathway linking connective tissue diseases and brain malformations.